DETEKSI DAN DIAGNOSIS TUBERKULOSIS LARING - Assa Putri Nur Anisya Anisya; Maria Angelika Tampubolon Tampubolon; Tiara Melati (Fakultas Kedokteran Universitas Trisakti, 2025)
Laryngeal tuberculosis, a form of extrapulmonary tuberculosis is prevalent less than 2% in Indonesia. Indonesia continues to be the second-highest tuberculosis-endemic country in the world, with more than 700,000 cases in 2022 and more than 600,000 cases in 2023. Of these cases, only 8% are extrapulmonary. In head and neck tuberculosis, laryngeal tuberculosis is the second most common manifestation after cervical lymphadenopathy tuberculosis. However, these numbers are expected to be underreported and underestimated in Indonesia. Misdiagnosis often occurs in highly contagious laryngeal tuberculosis due to lacking pathognomonic signs and symptoms. Furthermore, the high frequency of tuberculosis in productive age groups, particularly those aged 15 to 54 years, results in enormous catastrophic expenses for affected individuals, as well as a financial burden on the government. Considering the fore mentioned, a comprehensive systematic review of such rare case is required. This review aims to facilitate and provide an update on early detection and diagnosis of laryngeal tuberculosis to appropriate and prompt management.